(3efThQ fUQ GHf aJhMs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hUdJ ecGJHGJ GdTjN GdNjQ GdOjf CWGd Gddg ai Seh efRdJg HbGg hCMSf Yf MejO WGYJg hELJgGOg LRBg hhbaJ Ydi eG Sgd efgG s
(3BNQgG (B:s
(3hYQage Cf gPg GdecGJHI ef bHd hUhd cJGHc djYQahG efg hdi GdReGf hjJGOHhG HeG gh BJ hHeG bO cGf JeJ HefI hdi GdMb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B106s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis